Active peristaltic movements and fluid production of the mouse oviduct: their roles in fluid and sperm transport and fertilization†. Issue 1 (12th April 2019) - Hino, Toshiaki; Yanagimachi, Ryuzo
Abstract: To study how the oviduct behaves in relation to fluid secretion and sperm transport, ovary–oviduct–uterus complexes of the mouse were installed in a fluid-circulating chamber without disturbing the blood circulation or parasympathetic innervation. Injection of a bolus of Indian ink into the lower isthmus revealed very active adovarian peristalsis of the isthmus, which was most prominent during the periovulatory period. Oviduct fluid, secreted by the entire length of the isthmus, was rapidly transported to the ampulla and ovarian bursa before draining into the peritoneal cavity. The upper isthmus, in particular the isthmic–ampullary junction, was responsible for this adovarian fluid flow. Peristalsis of the oviduct, undisturbed flow of oviduct fluid from the isthmus to the peritoneal cavity, and the spermatozoon's own motility all contribute to efficient sperm ascent and to fertilization within the oviduct. Therefore, chemotaxis, rheotaxis, and thermotaxis of spermatozoa toward oocyte–cumulus complexes in the ampulla are all unlikely mechanisms for explaining sperm–oocyte contact and successful fertilization, given the rapid adovarian flow of oviduct fluid in this species. Abstract : Adovarian peristalsis of the oviduct, undisturbed oviduct fluid flow, and the spermatozoon's own motility all contribute to efficient sperm ascent and fertilization in the mouse oviduct.